2015
DOI: 10.1016/j.sbspro.2015.06.453
|View full text |Cite
|
Sign up to set email alerts
|

The Moderator Effect of Global Competitiveness Index on Dimensions of Logistics Performance Index

Abstract: The most important assessment tool that demonstrated the comparative situation of countries is Logistics Performance Index (LPI) created by World Bank. This index which has been prepared as a questionnaire consists of six dimensions. These dimensions are Customs: The efficiency of clearance process, Infrastructure: Quality of trade and transport related infrastructure, International Transportation: Capability of arranging competitively priced shipments, Logistics Competence: Competence and quality of Logistics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 1 publication
0
12
0
4
Order By: Relevance
“…Therefore, variables influencing the competitiveness of international transport are the quality of transport services, execution times, roads, ports, railways and airports, and traffic (which comprises tonnes, containers, goods in general). However, distances, costs, and transport infrastructure are the factors that have the greatest impact on competitiveness, even measured by the World Economic Forum (WEF) (Zamora & Pedraza, 2013;Çemberci, Civelek & Canbolat, 2015).…”
Section: Conceptual and Theoretical Backgroundmentioning
confidence: 99%
“…Therefore, variables influencing the competitiveness of international transport are the quality of transport services, execution times, roads, ports, railways and airports, and traffic (which comprises tonnes, containers, goods in general). However, distances, costs, and transport infrastructure are the factors that have the greatest impact on competitiveness, even measured by the World Economic Forum (WEF) (Zamora & Pedraza, 2013;Çemberci, Civelek & Canbolat, 2015).…”
Section: Conceptual and Theoretical Backgroundmentioning
confidence: 99%
“…Finally, we selected a direct competitiveness index, GCI, which is also officially measured/calculated by European countries. GCI, constructed and applied by the World Economic Forum, is accepted worldwide for indicating market and country competitiveness, including several transport-and logistics-related composites [28]. In our study, we applied GCI as an all-encompassing attribute related to competitiveness of each examined country, the second pillar of GCI related to rail infrastructure quality specifically and the sixth pillar related to market efficiency (The Global Competitiveness report 2011-2012).…”
Section: Theory/literature Overview On Competitiveness Factors Of Raimentioning
confidence: 99%
“…In some studies, the estimation of KPIs is also used as a reflection of logistics performance that may be affected by certain policy measures [20][21][22]. Cemberci et al [22] considered the effect of global competitiveness on the KPIs of transportation operators and concluded that better competitiveness could be achieved by timely improvement of the KPI components as well as through active monitoring of international shipments. Kim and Min [20] combined the KPIs and the environmental performance index to create an index of green logistics performance, which significantly influenced the final results of the research.…”
Section: Literature Reviewmentioning
confidence: 99%